Meaningful Learning in a New Paradigm for Educational Accountability: An Introduction - Linda Darling-Hammond; Jon Snyder (Arizona State University, 2015)
This special issue furthers the conversation begun in the August 2014 of edition of Education Policy Analysis Archives in the article Accountability for College and Career Readiness: Developing a New Paradigm by Linda Darling-Hammond, Gene Wilhoit and Linda Pittenger. That paper posits that as schools across the country take on the challenge of preparing all children for success in college, career, and life, states must in turn move toward creating more aligned systems of assessment and accountability. The authors recommend "an accountability approach that focuses on meaningful learning, enabled by professionally skilled and committed educators, and supported by adequate and appropriate resources, so that all students regardless of background are prepared for both college and career when they graduate from high school" (p. 1). This issue focuses particularly upon accountability for meaningful learning with subsequent issues focusing on professional accountability and resource accountability.